Meet the need: The role of vocational education and training for the youth labour market - Thomas Bolli; Maria Esther Egg; Ladina Rageth (ETH Zurich, KOF Swiss Economic Institute, 2017)
To fight negative trends in the youth labour market, policymakers around the world foster vocational education and training programmes (VET). We therefore investigate how the share of three upper secondary education programmes, i.e. general education, school-based VET, and dual VET, affect the labour market of 15- to 24-year-olds. We complement the existing literature by analysing non-linear effects that might arise due to general equilibrium effects. Furthermore, we include ten labour market indicators for integration and job quality. To address unobserved heterogeneity across countries, we run fixed effects regressions on unbalanced panel data of 35 countries from 2004 to 2014. We find that school-based VET hinders youth labour market integration. In contrast, dual VET improves not only labour market integration but also job quality. However, the positive and negative effects of VET programmes diminish with increasing enrolment rates. Thus, policymakers should consider these different effects in their educational reforms.
Keywords: I21; E24; J81; 330; Education System; Vocational Education and Training; Apprenticeship; Youth Labour Market; Unemployment